Foregut cystic developmental malformation: New taxonomy and classification - Unifying embryopathological concepts - Sharma Sharad; Nezakatgoo Nosratollah; Sreenivasan Prithvi; Vanatta Jason; Jabbour Nicolas (Wolters Kluwer Medknow Publications, 2009)
Foregut cystic developmental malformations are rare developmental anomalies. The problems inherent to these malformations are their presentation across specialties that include embryology, anatomy, pathology, thoracic foregut surgery, pediatric surgery and general abdominal surgery. The direct consequence of this variation has resulted in diverse terminology, classification and a failure to identify the correlation. The article aims to summarize and unify the embryological concepts of foregut cystic malformation, to suggest a generic title to the various groups of these interrelated disorders and a uniform use of nomenclature on the basis of unifying concepts of embryopathogeneis.